Impact of Various Ovulation Synchronization Protocols on Serum Triglycerides and Cholesterol Profile in Repeat Breeder Cows during Different Breeding Seasons - Manokaran, Sakthivelu; Napolean, Rayappan E.; Selvaraju, Mani; Balasubramaniam, Gurusamipalyam A.; Palanisamy, Mahakrishnan; Geetha, Thangavel (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study evaluated whether various ovulation synchronization protocols modulate cholesterol and triglycerides profile and enhance fertility in repeat breeding crossbred cows under field conditions. The study was conducted in 100 repeat breeder cows which were divided into five experimental groups, viz., Group I, II, III, IV (Treatment groups) and Group V (Control group) during the high breeding season (HBS: i.e., from October to March) and low breeding season (LBS: i.e., from April to September). Fifty cows were used during HBS and 50 cows during LBS. The Ovsynch, Presynch+Ovsynch, Ovsynch+Post-AI GnRH, and Ovsynch+Vitamin A protocols were followed to treat the Group I, II, III, and IV cows, respectively, and artificial insemination was performed during induced estrus. The group V cows were inseminated during observed estrus. There was an increasing trend in cholesterol concentration from selection to 7 days post-AI in all the groups in both HBS and LBS. Further, the cholesterol concentration was higher during HBS than LBS. The pregnant cows had significantly (p<0.05) higher mean (±SE) serum cholesterol levels than non-pregnant cows in both seasons. There was no much variation in serum triglycerides concentration between pregnant and non-pregnant cows. The study showed that the cholesterol concentration was affected by the season of the year, whereas the serum triglyceride concentration was not affected. The synchronization protocols used to affect the serum cholesterol concentration rather than serum triglycerides in repeat breeder cows during different seasons